Future Catastrophic Event Preparation: Recommendations From Clinical Nurses Aligning With the Future of Nursing 2020-2030 Report. (November 2022) - Robinson, Karen R.; Gierach, Michelle; Wolles, Brenda; McClellan, Coreen; Bartelt, Samantha; Hodge, Janel
Abstract : Nurses play an important role in pandemic and disaster response, often at a personal cost to their overall well-being. Interviews with 19 frontline COVID-19 nurses helped illuminate priority focus areas involving nurses in the planning process, providing clear communication and offering mental health services. These recommendations align with and reinforce conclusions and recommendations from The Future of Nursing 2020-2030 Report.